Forensic engineering of water leakages of underground structures. Issue 3 (2nd January 2019) - Kog, Yue Choong
Abstract : One of the main problems of underground structures is water leakage. Depending on the severity and extent of such water leakages, service lives of the affected underground structures may be adversely affected and maintenance costs throughout the service life will become much higher. Possible causes of water leakages of underground structures are poor workmanship of contractors and inherent weaknesses of waterproofing systems. Practising engineers investigating water leakages of underground structures should have a thorough understanding of various issues such as structural design and construction of the underground structures, waterproofing system, repair material and method, reforming of the waterproofing layer, inspection regime and periodic repair after the completed underground structure is in use. Currently, such an integrated discussion has yet to be reported in the literature. The purpose of this paper is to provide such a discussion by summarising the present know-how along with the author's 43 years of experience investigating the water leakage of underground structures. Other related issues such as the repair of cracks and autogenous healing of cracks are discussed.